Aplikasi Rekam Medis Pada Puskesmas Bulukandang Berbasis Android Dengan Metode Waterfall - Nur Khabib Fahrur Rozi; Imron Rosadi (Puslitbang Sinergis Asa Professional, 2023)
Medical records are patient record files containing patient examinations and examination histories from the initial patient treatment until they are needed again. At the Bulukandang Health Center, there are obstacles in the patient's medical record service, because recording is still carried out using a hybrid system. The hybrid filing system used by the Bulukandang Health Center is in the form of physical documents and archiving of paper documents. The purpose of this research is to create a Medical Record application at the Bulukandang Health Center based on Android. Before this application is built, this application is first designed using Figma. Then this medical record application was built using Android Studio software, accessing the data with get and post methods through the RESTFUL API. The Waterfall method is used in system development. Based on the results of Black Box testing the application built can be used without errors and bugs. Based on testing using the usability scale obtained a score of 81 from 10 respondents' responses, indicating that a score of 81 for the Acceptability Ranges version was obtained Acceptable. So that this application can help staff and employees of the health center, so that work is more effective and efficient.